Difficulties encountered by patients with breast cancer (Research, Society and Development, 2022)
This study aimed to identify the emotional/psychological and physical difficulties of patients with breast cancer, with the intention of understanding what interventions can be carried out to provide a better quality of life for these patients. This is an integrative review, where a search for articles was carried out in the SCIELO database, during the period from February to March 2022, using the descriptors in health sciences and Boolean operators in the respective sequence "Cancer AND Breast AND Assistance in health”, after which a total of 156 documents were obtained. After applying all the inclusion and exclusion criteria, a total of 14 articles were used in the preparation of the study. It was necessary to observe that there are several difficulties encountered by patients with the diagnosis of breast cancer that are linked to changes in the daily life and experiences of these women, bringing insecurities and physical and psychological changes. In view of this, it is concluded that breast cancer is a disease that affects several aspects of people's lives, causing complications that are difficult to cope with, making it necessary to conduct actions carried out by health teams that contribute to improving this situation.